A Luta Livre no Brasil: o conteúdo publicado pela mídia tradicional brasileira - Amaral, Carlos Cesar Domingos do (2022)
The Pro-Wrestling in Brazil is an entertainment sport that has been in the country for 60 years. His intention is to confront heroes and villains in combat that seeks to entertain and motivate the audience. Since the sport was successful, the traditional Brazilian media publishes about the shows, presentations and fighters. The objective of this thesis is to understand, from the theory of newsmaking, the articles about Pro-Wrestling in pre-established categories. In addition to thinking about this material from the perspective of infotainment and mediatization. The methodology used includes a literature review, document research, application of a questionnaire to content producers of Pro-Wrestling, and other methods. The main results show that newsmaking actually happens in news productions, but the act of researching the topic is not done properly and mistakes are made. Another striking feature in these materials is the high repetition of the modality's historical terms, which makes many productions to be repeated and without further elaboration. Finally, the traditional Brazilian media does not demonstrate the ability to report on Luta Livre due to the lack of knowledge of the sport. With most editorials being applied to infotainment, in which entertainment and information are mixed, Pro-Wrestling is reduced to something false. This demeans the efforts of everyone involved in the show.(AU)